2012
DOI: 10.1213/ane.0b013e318256858f
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Obesity on the ED95 of Propofol for Loss of Consciousness in Children and Adolescents

Abstract: A simple approach to deciding what dose of propofol should be used for induction of anesthesia in children ages 3 to 17 years is to first establish the child's BMI on readily available gender-specific charts. Obese children (BMI >95th percentile for age and gender) require a lower weight-based dose of propofol for induction of anesthesia, than do normal-weight children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…Hence clinical trials for evaluating propofol dosing in obese children is necessary. A recent retrospective study concluded that overweight/obese children are more likely to receive doses of common anesthetic medications outside recommended doses potentially adding risk of adverse outcomes in these children [61]. Ingrande et.…”
Section: ) Propofol Pharmacokinetics (Pk) and Pharmacodynamics (Pd) mentioning
confidence: 99%
“…Hence clinical trials for evaluating propofol dosing in obese children is necessary. A recent retrospective study concluded that overweight/obese children are more likely to receive doses of common anesthetic medications outside recommended doses potentially adding risk of adverse outcomes in these children [61]. Ingrande et.…”
Section: ) Propofol Pharmacokinetics (Pk) and Pharmacodynamics (Pd) mentioning
confidence: 99%
“…Examples of BCD in anesthesia studies include identifying the minimum effective dose of lidocaine or ropivacaine needed to effectively block the femoral nerve in 90% of subjects. Pediatric anesthesia examples include determining the speed of a propofol bolus at induction preserving respiration , finding an ED 95 dose of remifentanil allowing extubation without coughing post tonsillectomy , or determining the effect of obesity on ED 95 for propofol during induction .…”
Section: Sequential Design Methodsmentioning
confidence: 99%
“…4 When evaluating the alterations of pharmacokinetics on the drug propofol, obese children require significantly less propofol for loss of lash reflex than do lean children; obese children are given a lower dose of propofol on the basis of actual body weight than their nonobese peers. 10 Clearance of propofol appears to be linearly related to lean body weight rather than to total body weight. 5 It is recommended that the dose of propofol for both induction and maintenance of anesthesia should be based on actual body weight in obese individuals analogous to their lean counterparts.…”
Section: Management Of Anesthesia Of the Obese Patient Inductionmentioning
confidence: 96%